Solvent-free cellulose nanocrystal fluids for simultaneous enhancement of mechanical properties, thermal conductivity, moisture permeability and antibacterial properties of polylactic acid fibrous membrane. (1st October 2021) - Shen, Hui; Li, Yushan; Yao, Wei; Yang, Shiwen; Yang, Ling; Pan, Fei; Chen, Zhenming; Yin, Xianze
Abstract: The simultaneous achievement of ultrafast water vapor transport and evaporation, robust mechanical properties, rapid heat dissipation, and excellent antibacterial activity is still highly challenging for advanced bio-based degradable textile composites. Herein, multifunctional biodegradable composite fibers were designed via converting the cellulose powder into solvent-free spherical cellulose crystal fluids (CNCfs) followed by embedding into bio-based polylactic acid (PLA) fibrous membrane using the electrospinning. By taking full advantage of the low viscosity, amphiphilicity and high dispersion of CNCfs, the as-prepared bio-based fibrous membranes with tunable surface chemical and excellent mechanical properties (simultaneous plasticizing and reinforcement) were obtained. Due to the unique bilayer ion structure of the CNCfs located on the surface of PLA fiber after the electrospinning process, the fibrous membrane shows prominent superhydrophilicity (water contact angle of 0°) along with enhanced absorption water capacity and water vapor transmission rate (WVTR) of 3.612 kg m −2  h −1 (81 times higher than the pure PLA fibrous membrane). Moreover, the hygroscopicity-inspired design also endows PLA/CNCfs fibrous membrane with antistatic performance, rapid heat dissipation (decreased by 2 °C relative to the PLA bulk) with high thermal conductivity of 0.27 W/mK and excellent antibacterial activity of 98.5% and 92.7% against E. coli and S. aureus, respectively. Overall, this facile and effective strategy provides a promising route for the fabrication of multifunctional biodegradable fibrous membranes for use in environmental-friendly medical textiles, personal protection and human health applications.